Penerapan Model Pembelajaran Tuntas (Mastery Learning) Pada Materi Konsep Mol di SMA Negeri 1 Remboken - Fritson Linggot; Meytij Rampe; Jenny Kumajas (Oxygenius Journal Of Chemistry Education, 2022)
This research is an experimental research with Mastery Learning model. This study aims to determine the effect of the Mastery Learning model on student learning outcomes on the mole concept material. This research was conducted in class X SMA Negeri 1 Remboken with a sample of 57 people. The research design used is the post-test-only control group design experimental method. The experimental class uses a complete learning model and the control class uses a conventional learning model. Analysis of hypothesis testing using t-test with a significant level = 0.05, because with a two-way test then the value of a/2 = 0.025. The test results obtained show that the results of t arithmetic > t table or 9.02 > 2.05, thus H0 is rejected and H1 is accepted, this indicates that there is a significant difference between the average value (post-test) of the experimental group and the experimental group. control group experiment. So it can be concluded that there is a difference in the average learning outcomes of students who are taught the mastery learning model with the learning outcomes of students who are taught conventional learning on the mole concept material.